KEUNGGULAN KOMPARATIF KOMODITAS JAGUNG DI KABUPATEN KEDIRI - Navita Maharani (Universitas Islam Kadiri, 2017)
This research was conducted to determine the comparative advantage of maize. The analysis method to answer the research objective is Domestic Resource Cost (DRC) analysis. The results said that maize in Kediri has a comparative advantage. Maize farming using domestic resources can save foreign exchange of US 0.538 per unit of US 1 imported. So it is better that maize was produced in own country using the domestic resources rather than imported to meet the needs of the national maize. the decline in maize productivity have a negative impact on the level of comparative advantage. Even if it continue to decline, maize can be lose the value of comparative advantage